THE INFLUENCE OF WORK DISCIPLINE AND COMPETENCE ON JOB SATISFACTION MEDIATED BY EMPLOYE PERFORMANCE AMONG PUBLIC AND PRIVATE KINDERGARTEN TEACHERS IN BANTEN PROVINCE - Ratnaningsih, Ratnaningsih; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
This study aimed to examine the influence of work discipline and competence on job satisfaction, with employee performance as a mediating variable, among public and private kindergarten teachers in Banten Province. Performance issues posed challenges for organizations, requiring strategies such as improving discipline, competence, and satisfaction. The hypotheses proposed that work discipline and competence positively and significantly affected job satisfaction and performance, while job satisfaction positively influenced performance. Employee performance was also expected to mediate the effects of work discipline and competence on job satisfaction. A quantitative approach was applied using Slovin’s formula, involving 200 respondents from 401 ASN kindergarten teachers. Data were analyzed through path analysis. Results showed: (1) work discipline significantly affected job satisfaction (β = 0.334; t = 3.177); (2) competence significantly affected job satisfaction (β = 0.442; t = 4.830); (3) work discipline significantly affected performance (β = 0.441; t = 3.636); (4) competence had no significant effect on performance (β = 0.086; t = 0.887); (5) performance significantly affected job satisfaction (β = 0.444; t = 4.995). Employee performance mediated the effects of work discipline (β = 0.254; t = 3.082; p < 0.05) and competence (β = 0.235; t = 2.717; p < 0.05) on job satisfaction. These findings indicate that improving discipline and competence, supported by optimal performance, enhances job satisfaction among ASN kindergarten teachers in Banten Province.